Prinsip dan Ajaran Tasawuf ‘Abd Allâh al-Haddâd - Fikri Mahzumi (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2012)
‘Abd Allâh al-Haddâd is a prominent figure who greatly influences many parts of the world, including Indonesia. His mystical teachings (tasawwuf), which are Sunni, akhlâqî and ‘amalî, are oriented to guide society's morality and, therefore, are more acceptable. A variety of his work, both in the form of books, wird, kasidah, and his Râtib are widely spread and practiced by many people, especially his followers. Al-Haddâd’s mystical orientation also emphasizes the socio-moral movement. Among his mystical teachings are science, charity, khawf, wara‘, and sincerity which are based on al-Qur’ân, the Sunnah of the Prophet, and the example of the pious Salaf. Here, al-Haddâd was able to make renewal in the field of Sufism by reforming the segment and the orientation of the tarekat. If in the past tarekat was only familiar to elites, it then has been converged by al-Haddâd into two different segments, i.e., the tarekat of elite and the tarekat of public, with the same orientation that is approaching to God. Through this reorientation, al-Haddâd had attempted to present Sufism as a social movement that raises morale for both individuals and social groups.